2015
DOI: 10.3851/imp3039
|View full text |Cite
|
Sign up to set email alerts
|

Aminomethylnaphthoquinones and HSV-1: in vitro and in silico Evaluations of Potential Antivirals

Abstract: Since resistance is still a problem for treating HSV infections, these compounds present a promising profile toward the development of new strategies for anti-HSV-1 therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Previous studies with 2-aminomethyl-3 hydroxy 1,4 naphthoquinones, carrying butyl and benzyl substitutions, found that they were the most promising compound against HSV-1, with SI values of 1.52 and 1.16, respectively, which are higher than ACV (SI = 0.80). The same effectiveness was observed with nitrobenzene derivative in the inhibition of BoHV-5 replication, demonstrating possibly different targets in the same viral family, despite the same control on the early and late phases of replication [36,38] Furthermore, pre-clinical studies with BALB/c demonstrated that the oral administration of compound 1 (butyl) has no effect on transaminases level or kidneys functions, excluding possible side effects after the oral administration of the substance [37].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Previous studies with 2-aminomethyl-3 hydroxy 1,4 naphthoquinones, carrying butyl and benzyl substitutions, found that they were the most promising compound against HSV-1, with SI values of 1.52 and 1.16, respectively, which are higher than ACV (SI = 0.80). The same effectiveness was observed with nitrobenzene derivative in the inhibition of BoHV-5 replication, demonstrating possibly different targets in the same viral family, despite the same control on the early and late phases of replication [36,38] Furthermore, pre-clinical studies with BALB/c demonstrated that the oral administration of compound 1 (butyl) has no effect on transaminases level or kidneys functions, excluding possible side effects after the oral administration of the substance [37].…”
Section: Discussionmentioning
confidence: 87%
“…The time of addition assay is a common approach for determining how long the addition of a specific compound could remain efficient for controlling viral replication in cell culture. For this purpose, in order to compare if liposomes were also able to inhibit the early and late phases of HSV-1 replication, we used protocols, already published by our group, with free derivatives [38]. Briefly, after initial HSV-1 infection with 0.1 MOI, Vero cells were washed with PBS and incubated with MEM 5%BFS for 3 h post infection (hpi) or 6 hpi at 37 • C. Subsequently, the medium was replaced by naphthoquinone derivatives, and acyclovir was encapsulated into liposomes with concentrations corresponding to four times the EC 50 values for an additional 3 h or 14 h of incubation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3-(Aminomethyl)-2-hydroxy-1,4-naphthoquinones known as aminonaphthoquinone Mannich bases, constitute an interesting class of naphthoquinones and/or their metal complexes have demonstrated a series of important biological properties such as anticancer, 22 antimalarial, 23 antimolluscicidal, 24 antibacterial, 25 cholinesterase inhibitors, 26 leishmanicidal, 27 antiviral, 28 antifungal, 29 anti parasitic 30 activities and they have also been employed as uorescent compounds and dyes. 31 Because of their prevalent applications, several methods have been reported for the synthesis of these important compounds and their metal complexes.…”
Section: Introductionmentioning
confidence: 99%